P0308IMPACT OF MAJOR SURGICAL OPERATIONS ON CLINICAL OUTCOME IN DIALYSIS PATIENTS. (6th June 2020) - Eren Sadioğlu, Rezzan; Kumru Şahin, Gizem; Kutlay, Sim; Şengül, Şule; Keven, Kenan; Nergizoglu, Gökhan; Ateş, Kenan; Duman, Neval; Ertürk, Şehsuvar
Abstract: Background and Aims: We aimed to study the impact of major surgical operations on clinical outcome in patients with end-stage kidney disease treated with haemodialysis (HD) or peritoneal dialysis (PD). Method: We retrospectively evaluated the records of all patients on HD and PD, who had been treated for at least 3 months at our outpatient clinics between January 1, 2014 and December 31, 2018. In addition to clinical and laboratory parameters, data on all major surgical operations were recorded. Results: Among the 202 patients, 133 (66%) were on HD and 69 (34%) on PD. The mean age (±SD) was 58.3±14.5 years, 48% were female and 28% had diabetes mellitus. Forty-seven patients (23%) had a major surgical operation. The operation types were cardiovascular in 14 patients, orthopaedic in 11, gastrointestinal in 8, genitourinary in 6, parathyroidectomy in 5 and brain, pulmonary and breast in 1 patient each. Operations were emergent in 10 patients (21%) and elective in the others (79%). Among the whole study population, 59 patients (29%) died during the study period. In Kaplan-Meier analysis (Figure), mean (95% CI) survival time in operated patients was 43 months (37 to 49 months), while it was 49 months (46 to 52 months) in the others (p=0.023). Fifteen out of 23 deaths (65%) among the operated patients occurred in the first month after surgery. Severe perioperative complications (arrhythmias, hypervolemia, hypotension, bleeding, acute coronary syndrome, respiratory failure and cerebrovascular event) were recorded in 17 (36%) of the operated patients, of whom 16 died (p=0.001). Although did not reach a significant level, mortality rate tended to be higher after emergent operations than that after elective operations. Cox regression analyses revealed that age (RR 1.033, 95% CI 1.010-1.057, p=0.005), diabetes (RR 2.581, 95% CI 1.474-4.521, p=0.001), preoperative C-reactive protein level (RR 1.005, 95% CI 1.002-1.007, p<0.0001) and having a major surgical operation (RR 1.868, 95% CI 1.068-3.268, p=0.028) were the independent predictors of mortality. Conclusion: Although prospective studies with a higher patient number are needed to confirm, our study shows that, in addition to age, diabetes and inflammatory status, having a major surgical operation is an independent risk factor for mortality in dialysis patients. The prevention and management of perioperative complications properly may result in more favourable outcomes in these patients.